Assessment of integration of methane-reduced ceria chemical looping CO2/H2O splitting cycle to an oxy-fired power plant. (28th February 2020) - Farooqui, Azharuddin; Bose, Archishman; Boaro, Marta; Llorca, Jordi; Santarelli, Massimo
Abstract: In this paper, we investigated the effect of reaction kinetics and moving bed reactors for chemical looping (CO2 /H2 O) splitting unit (CL) that produces syngas and fed back to the power plant to gain the efficiency loss due to carbon capture. The reduction reactor (RED) produces methane is partially oxidized to make syngas and reducing the non-stoichiometric ceria which is transported to oxidation reactor (OXI) where the flue gases (CO2 and H2 O) split to produce syngas. We developed the kinetics for methane reduced ceria and CO2 /H2 O splitting in a tubular reactor for an operating temperature range of (900–1100 °C) for different methane concentration which yielded to Avrami-Erofeev (AE3) model fits well for both redox reaction with different reaction constants. A moving bed reactors system is developed representing RED and OXI reactors of CL unit with kinetics hooked to the model in Aspen Plus with FORTRAN code. The effect of thermodynamics and the kinetics of redox reaction was investigated in the proposed integrated plant. The CL unit efficiency obtained is 42.8% for kinetic-based CL unit compares to 64% for thermodynamic based CL unit. However, the maximum available efficiency of the proposed layout lowered as 50.9% for kinetic-based CL unit plant compare to than 61.5% for thermodynamic based CL unit. However, the proposed plant shows an improvement in the energy efficiency penalty from 11.3% to 3.8% after CCS. Graphical abstract: Image 1 Highlights: Kinetic study of methane-driven CO2 /H2 O (CL) splitting is investigated. Redox reaction kinetics found to follow Avrami-Erofe'ev model. A moving bed CL unit is integrated to oxy-fired plant for efficiency improvement. The CL efficiency found to be 42.8% with system efficiency of 50.9%.